Analysis of Performance, Emission, Noise and Vibration on Single Cylinder Diesel Engine After Installing Dual Fuel Converter-Kit Based on ECU - Adhi Iswantoro; I Made Ariana; Muhammad Syuhri (Department of Naval Architecture - Diponegoro University, 2022)
Now the demand for fuel oil has increased, this can cause fuel oil reserves to be depleted. To reduce the use of fuel oil, alternative energy is needed. One alternative energy that can be used to reduce fuel oil consumption is LPG (Liquid Petroleum Gas). The use of alternative fuels for LPG in diesel engines is done by converting diesel engines into dual fuel. This research aims to determine the effect of using dual fuel that are LPG-Diesel fuel on engine performance including power, torque, fuel consumption, emissions, vibration and noise. The research was conducted using a Yanmar TF 85 MH engine at 2000 RPM engine speed with variations in loading of 1000, 1500, 2000, 2500, and 3000 watts, and dual fuel with variations in injector openings of 3ms, 4ms, 5ms. Based on the research results, the use of LPG in dual fuel system with installing ECU (Electronic Control Unit) converter-kit, can replace diesel fuel oil consumption up to 93%. In the use of dual fuel there is an average decrease in power and torque of up to 1.95% if using only diesel fuel have average power up to 2.32 kW and torque up to 11.09 Nm. When using dual fuel there is a decrease in specific fuel oil consumption by up to 44% when using only diesel fuel have average fuel oil consumption up to 414.15 g/kWh. The maximum NOx emission produced is 1.83 g/kWh for a 3ms gas injector opening, 1.48 g/kWh for a 4ms gas injector opening, and 1.81 g/kWh for a 5ms injector opening. The maximum vibration generated is 33.2 m/s² for a 3ms injector opening, 31.4 m/s² for a 4ms injector opening, 27.46 m/s² for a 5ms injector opening, and when used only Diesel Fuel is 32.8 m/s2. The maximum noise generated is 92.33 dBA for 3ms injector opening, 92.43 dBA for 4ms injector aperture, 93.20 dBa for 5ms injector aperture, and 91.73 dBa when using diesel oil only.